ChatGPT as the linguo-creative resource for teaching English language - Nauryzbayeva, A.B.; Bimagambetova, Zh.T. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This scientific article explores the potential of ChatGPT, a language model based on AI, as a linguo-creative resource for teaching English language in Kazakhstan. The authors conducted a mixed-methods study that included semi-structured interviews with 25 language teachers and learners, as well as an online survey that received 250 responses. The study aimed to provide a contextual understanding of the potential use of ChatGPT in language education in Kazakhstan, taking into account the unique cultural and linguistic features of the country. The authors analyzed the data using thematic analysis and descriptive statistics and chi-square tests. The results of the study showed several benefits and challenges associated with using ChatGPT, potential applications of ChatGPT in language education in Kazakhstan, and positive perceptions of language teachers and learners towards AI-powered tools in language education. The mixed-methods approach provided a more nuanced and comprehensive analysis of the potential use of ChatGPT in the context of Kazakhstan and contributes to the growing body of knowledge on the use of AI-powered tools in language education in diverse cultural and linguistic settings. The findings of the study can provide insights for language teachers and educators of Kazakhstan and other countries on the use of ChatGPT and other AI-powered tools for language learning and teaching.
ChatGPT ағылшын тілін оқытуға арналған лингвошығармашылық ресурс ретінде
ChatGPT как лингвокреативный ресурс для преподавания английского языка
Keywords: technology; artificial intelligence; ChatGPT; teaching English; Kazakhstan; mixed-methods study; language teachers; learners; potential applications